Early deterioration assessment of selected reinforcement in different host environments, case study: Lagos State, Nigeria. Issue 1 (1st January 2019) - O. Olukanni, David; Ige, Babatunde; O. Bamigboye, Gideon; Durodola, Bamidele
Abstract: Corrosion is known to negatively affect the structural integrity of reinforced concrete structures. In order to manage the effect of corrosion on structures, some preventive measures must be considered. Among such measures is to test the integrity of the reinforcement used. Three high-yield reinforcements mostly used in Lagos State (Pulkit, LCI and Tiger Thermo Mechanically Treated (TMT)) of three different diameters (12, 16 and 20 mm) were assessed for early deterioration in the reinforced concrete structure. The resistive strengths of Pulkit, LCI and Tiger TMT for the diameters considered were also assessed using gravimetric and electrochemical corrosion techniques in four host environments: freshwater, 1.0 M of NaCl solution, 1.0 M of KCl solution and seawater for a period of 35 days of exposure. The experimental results revealed that Tiger TMT for the three diameters displayed the least corrosion rate with the highest resistive properties. This makes it most suitable for concrete reinforcement in all the three selected media, while LCI shows a high corrosion rate with lower resistive behaviour only in the KCl solution. Pulkit results show the highest corrosion rate with the lowest resistive strength in all the environments. For the sustainability of concrete structures in the Lagoon environment that has some level of salt solution, Tiger TMT is mostly recommended for construction.